Quality of tuna fish oils extracted from processing the by-products of three species of neritic tuna using supercritical carbon dioxide - Ferdosh, Sahena; Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Oliveira, Alexandra; Yunus, Kamaruzzaman; Chowdury, Ahmed Jalal; Akanda, Jahurul H.; Omar, Mohd (Wiley-Blackwell, 2014)

(untitled)
Fatty acid constituents of total lipids extracted from the head, the skin and the viscera of three neritic tuna species, namely Thunnus tonggol, Euthynnus affinis and Auxis thazard, using supercritical carbon dioxide (SC-CO2) and Soxhlet extraction method were determined and compared. Saturated fatty acid (39.7– 48.5%) was dominant in conjunction with monounsaturated fatty acid (21.9– 26.6%) and polyunsaturated fatty acid (PUFA) (24.1–27.9%) in all species, and the difference between methods were nonsignificant. Docosahexaenoic acid was the major PUFA, accounting for 17.0–19.9% in the head, 15.7–17.3% in the skin and 14.3–16.1% in the viscera of total fatty acids. Total oil extracted by SC-CO2 had lower free fatty acid (FFA) and peroxide value (PV) content than that by Soxhlet method. The ranges of FFA and PV were 1.8–5.0 and 1.2–2.4%, respectively. It was concluded that SC-CO2 is an effective method to extract fish oil that is rich in omega-3 fatty acids from tuna by-products.